An Artificial Pathway for N-Hydroxy-Pipecolic Acid Production From L-Lysine in Escherichia coli - Luo, Zhou; Wang, Zhen; Wang, Bangxu; Lu, Yao; Yan, Lixiu; Zhao, Zhiping; Bai, Ting; Zhang, Jiamin; Li, Hanmei; Wang, Wei; Cheng, Jie (Frontiers in Microbiology, 2022)
N-hydroxy-pipecolic acid (NHP) is a hydroxylated product of pipecolic acid and an important systemic acquired resistance signal molecule. However, the biosynthesis of NHP does not have a natural metabolic pathway in microorganisms. Here, we designed and constructed a promising pathway in Escherichia coli for the first time to produce NHP from biomass-derived lysine. This biosynthesis route expands the lysine catabolism pathway and employs six enzymes to sequentially convert lysine into NHP. This artificial route involves six functional enzymes coexpression: lysine α-oxidase from Scomber japonicus (RaiP), glucose dehydrogenase from Bacillus subtilis (GDH), Δ1-piperideine-2-carboxylase reductase from Pseudomonas putida (DpkA), lysine permease from Escherichia coli (LysP), flavin-dependent monooxygenase (FMO1) and catalase from Escherichia coli (KatE). Moreover, different FMO1s are used to evaluate the performance of produce NHP. 111.06 mg/L of NHP was yielded in shake flasks with minimal medium containing 4 g/L lysine. By this approach, NHP has so far been produced at final titers reaching 326.42 mg/L by 48 h in 5-L bioreactor. To the best of our knowledge, this is the first NHP process using Escherichia coli and the first process to directly synthesize NHP by microorganisms. This study lays the foundation for the development and utilization of renewable resources to produce NHP in microorganisms.